Using bismuth oxycarbonate particles to filter ultraviolet light
Bismuth oxycarbonate particles address the cosmetic drawbacks of conventional UV screening agents by offering effective UV protection without a white cast, maintaining skin transparency and comfort, suitable for cosmetic compositions.
Patent Information
- Application Number
- JP2024536526
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional inorganic UV screening agents like titanium dioxide and zinc oxide used in sunscreens leave a white cast on the skin, causing cosmetic issues and reducing transparency, while reducing their concentration to avoid this effect compromises UV protection efficacy.
Employing bismuth oxycarbonate particles with an empirical formula (BiO)2-x(CO3) (-0.4
Bismuth oxycarbonate particles offer efficient UV protection, especially in the UVB range, with high transparency in the visible light spectrum, maintaining cosmetic properties and avoiding skin dryness and whiteness, suitable for use in cosmetic compositions.
Smart Images

Figure 2025501539000007 
Figure 2025501539000008 
Figure 2025501539000009
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of sun protection, and more particularly to the use of certain bismuth oxycarbonate particles to filter ultraviolet radiation.
[0002] Another subject of the invention is a composition, in particular a cosmetic composition, in particular a composition, in particular a cosmetic composition, comprising specific bismuth oxycarbonate particles.
[0003] Keratinous materials are exposed to sunlight every day.
[0004] It is known that rays with wavelengths between 280nm and 400nm can tan the human epidermis. However, rays with wavelengths between 280nm and 320nm (referred to as UVB rays) are harmful to the development of natural tanning. This exposure can also cause damage to the biomechanical properties of the epidermis, which is reflected by the appearance of wrinkles and leads to premature aging of the skin.
[0005] It is also known that UVA rays, with wavelengths between 320 and 400 nm, penetrate deeper into the skin than UVB rays. UVA rays promote rapid and persistent skin pigmentation. Under normal conditions, daily exposure to UVA rays, even for short periods, damages collagen fibers and elastin, which is reflected by changes to the skin's microstructure, the appearance of wrinkles, and uneven pigmentation (i.e., liver spots, uniformity of the complexion, etc.).
[0006] Moreover, prolonged exposure to the sun also dries out hair, making it brittle.
[0007] It is therefore of utmost importance to protect keratinous materials, particularly human keratinous materials such as the skin. [Background technology]
[0008] To counter these undesirable effects, it is routine to incorporate organic and / or inorganic anti-UVA and / or anti-UVB screening agents into compositions intended to provide sun protection.
[0009] Many skin photoprotective cosmetic compositions have been proposed up to now. They generally contain organic and / or inorganic UV screening agents, which act according to their own chemical properties and their own physical properties by absorbing, reflecting or scattering UV radiation. They generally contain organic UV screening agents that are soluble in oil, and / or a combination of water-soluble organic UV screening agents with metal oxide pigments, such as titanium dioxide (TiO2) or zinc oxide (ZnO).
[0010] As regards conventional organic screening agents, they must have acceptable cosmetic properties, good solubility in conventional solvents, especially in oils, and also good stability, either alone or in combination. They must also be colorless or have a color that is cosmetically acceptable to consumers. These organic screening agents are generally used in mixtures, and such combinations of screening agents may limit the formulation range.
[0011] In addition, today, consumers consider mineral sunscreens to be safer, so photoprotection using inorganic UV screening agents has become a very important consumer expectation.
[0012] TiO2 and ZnO are the most commonly used mineral UV screening agents.
[0013] Nevertheless, one of the major drawbacks of such mineral screening agents is that once applied to the skin, they cause a whitening effect which is cosmetically unpleasing and generally not particularly appreciated by users.
[0014] This effect is even more pronounced when the concentration of mineral screening agents in the composition is high, thereby limiting their concentration in sunscreen formulations.
[0015] To circumvent this problem, it is of course possible to use reduced amounts of one or more inorganic screening agents, but the resulting composition, although certainly resulting in a film that exhibits acceptable transparency on the skin, then no longer provides adequate protection in the UV range, thereby greatly limiting the benefit of such an option.
[0016] Moreover, apart from a noticeable white cast effect, the use of large amounts of these UV screening agents leads to an unpleasant sensation after application to the skin, resulting in a sensation of roughness and dryness of the skin, especially if the products are used in large amounts and regularly.
[0017] Consumers are increasingly looking for products that are effective, yet extremely easy to apply, have long-lasting comfort and satisfying organoleptic properties. Summary of the Invention [Problem to be solved by the invention]
[0018] Thus, there remains a need for inorganic UV screening agents which provide efficient photoprotection and which do not have the disadvantages mentioned above.
[0019] In particular, it is possible to efficiently block ultraviolet rays, particularly in the UVA and UVB ranges, particularly UVB rays, which have high transparency in visible light, do not whiten the keratin substances to which they are applied, and there is still a need for inorganic UV screening agents that have good cosmetic properties.
[0020] There is a particular need for mineral UV screening agents other than titanium dioxide or zinc oxide that have an equivalent effect, are transparent, do not cause a feeling of roughness and dryness on the skin, and are easy to formulate, particularly at high concentrations.
[0021] The present invention particularly aims to propose the use of a novel mineral UV screening agent that makes it possible to meet these expectations.
Means for Solving the Problems
[0022] Therefore, according to its first aspect, the present invention relates to the use of bismuth oxycarbonate particles having the following empirical formula (BiO) 2-x (CO3) (where -0.4 < x < 0.6) for filtering ultraviolet irradiation, wherein the maximum average dimension of the particles is less than 400 nm, and the above use is provided.
[0023] Preferably, the maximum average dimension of the particles is 300 nm or less.
[0024] Preferably, the bismuth oxycarbonate particles are crystallized.
[0025] According to a preferred embodiment, the present invention relates to the use of the particles for filtering UVB irradiation.
[0026] Surprisingly, and as will become apparent from the examples below, the inventors have discovered that bismuth oxycarbonate particles having the specific size required according to the invention have excellent efficacy for filtering ultraviolet radiation, in particular UVB rays, and high transparency in the visible range, enabling compositions containing them to impart satisfactory cosmetic properties to the consumer.
[0027] For the purposes of the present invention, "high transparency in the visible range" means particles that have a high transmittance of light rays between 400 and 780 nm.
[0028] For the purposes of the present invention, "effectiveness for filtering ultraviolet radiation" refers to particles that have a threshold absorbance in the UV range of greater than 0.5, preferably greater than 1.0, more preferably greater than 1.5 in a dispersion medium containing the particles. The higher the threshold absorbance, the more effective the particles are at filtering UV radiation. The higher the threshold absorbance, the more effective the particles are at filtering UV radiation.
[0029] UVB radiation means the wavelength range extending from 280 to 320 nm. UVA radiation means the wavelength range extending from 320 to 400 nm. Visible light means the wavelength range extending from 400 to 780 nm.
[0030] Thus, for purposes of the present invention, "UV screening agent" is intended to denote any compound that filters ultraviolet (UV) radiation in the wavelength range ranging from 280 nm to 400 nm. "UVB screening agent" is intended to denote any compound that filters ultraviolet (UV) radiation in the wavelength range ranging from 280 nm to 320 nm. "UVA screening agent" is intended to denote any compound that filters ultraviolet (UV) radiation in the wavelength range ranging from 320 nm to 400 nm.
[0031] This efficacy of bismuth oxycarbonate particles, especially crystallized bismuth oxycarbonate particles, has been characterized for the first time to the best of the inventors' knowledge. The use of bismuth oxycarbonate particles in cosmetic compositions intended for the effective filtering of ultraviolet rays, especially UVB irradiation, has not been proposed heretofore.
[0032] The bismuth oxycarbonate particles required according to the present invention are especially intended to protect keratinous substances, especially the skin and hair, from ultraviolet rays, especially in cosmetic compositions for the fields of sunburn prevention, hair care or treatment, and makeup.
[0033] Accordingly, from another aspect, the present invention also relates to a non-therapeutic cosmetic method for filtering UV irradiation, especially UVB irradiation, which comprises at least applying a composition containing the bismuth oxycarbonate particles defined above to a keratinous substance.
[0034] "Keratinous substance" especially means the skin, including the skin such as the scalp and lips, and also keratin fibers such as hair, eyelashes and eyebrows, especially means the skin and / or hair, preferably the skin.
[0035] According to another of those aspects, the present invention also relates to a composition, especially a cosmetic composition, i) bismuth oxycarbonate particles having the following empirical formula (BiO) 2-x (CO3) (where -0.4 < x < 0.6), wherein the maximum average dimension of the particles is less than 400 nm; ii) at least one aqueous phase and / or at least one fatty phase; and, iii) at least one compound selected from a) UV screening agents other than the bismuth oxycarbonate particles i); b) colorants; c) cosmetic active agents for caring for keratinous substances; d) surfactants; e) thickeners; and combinations thereof relates to the above composition comprising at least.
[0036] The term "at least one" is equal to "one or more".
[0037] The expressions "... to...", "... including...", "formed from... to...", and "range from... to..." should be understood as including the limiting values, unless otherwise specified.
[0038] Other features, variations, and advantages of the compositions according to the present invention will become more clearly apparent by reading the following detailed description of the invention and the examples.
Mode for Carrying Out the Invention
[0039] The present invention relates to the use of bismuth oxycarbonate particles of the following formula (I) as an agent for filtering ultraviolet radiation, particularly UVB radiation.
[0040] Bismuth oxycarbonate particles As described above, the bismuth oxycarbonate particles according to the present invention have the following empirical formula (BiO) 2-x (CO3) (where -0.4 < x < 0.6). The value of x can be determined, in particular, by elemental analysis.
[0041] Preferably, x is equal to 0, and the empirical formula of the bismuth oxycarbonate particles is (BiO)2(CO3).
[0042] The bismuth oxycarbonate particles according to the present invention can be crystallized or can be amorphous.
[0043] According to one embodiment of the present invention, the bismuth oxycarbonate particles are amorphous.
[0044] According to a preferred embodiment of the present invention, the bismuth oxycarbonate particles are crystallized.
[0045] It will be understood that the bismuth oxycarbonate particles may consist of a mixture of several bismuth oxycarbonate particles having different empirical formulas and / or different shapes.
[0046] Thus, the bismuth oxycarbonate particles can be a mixture of amorphous and crystallized particles.
[0047] For purposes of this invention, "crystallized" means that the atoms forming the bismuth oxycarbonate particles are arranged in an ordered manner. In other words, the crystallized bismuth oxycarbonate particles are organized materials.
[0048] In contrast, an "amorphous" particle is one in which the atoms are disordered: the atoms of such a particle do not show any organization in the microscopic state.
[0049] Preferably, the crystallized particles required according to the invention have the crystalline phase of natural ore bismutite, referred to as lamellar, which is [Bi2O2] 2+ and [CO3] 2- The layer has alternating layers of
[0050] Such particles crystallize in the orthorhombic system, in the space group Imm2.
[0051] The bismutite crystal structure of bismuth oxycarbonate can have the following lattice parameters: a=3.865 Å; b=3.862 Å; c=13.675 Å and V lattice =0.204nm 3 This particular atomic arrangement in particular allows for the growth of anisotropic objects.
[0052] When the elongation factor R between the length L and the thickness e of the particles, that is, R = L / e, exceeds 2, the particles are considered to be "anisotropic".
[0053] Particle dimensions According to the present invention, the maximum average dimension of the crystallized or amorphous bismuth oxycarbonate particles having the following empirical formula (BiO) 2-x (CO3) (where -0.4 < x < 0.6), preferably crystallized bismuth oxycarbonate particles, is less than 400 nm for -0.4 < x < 0.6.
[0054] Preferably, the maximum average dimension of the particles is 300 nm or less.
[0055] "Average dimension" is intended to indicate the number average value of the dimensions of the particles. The dimensions of the particles can be determined, for example, by transmission electron microscopy, scanning electron microscopy using a Hitachi HT7700 microscope, particularly at an acceleration voltage of 100 kV, or by measurement of the specific surface area via the BET method, or else using a laser particle size analyzer. The number average value can be calculated by analyzing an image obtained using software, such as ImageJ software (C.A. Schneider, W.S. Rasband, K.W. Eliceiri, NIH Image to ImageJ: 25 years of image analysis, Nat. Methods. 9 (2012) 671 - 675).
[0056] The average dimension is selected from the average length L, average width l, average thickness e, or average diameter d.
[0057] The "maximum average dimension" of the particles is intended to indicate the maximum average dimension of a surface, such as a face, that can be measured between two diametrically opposed points on an individual particle.
[0058] The "length" L of the particle is the maximum dimension of the particle that can be observed in an image taken in a direction perpendicular to the plane in which the particle is placed.
[0059] The "width" l and "thickness" e of the particle are the lengths of the major axis and minor axis of the smallest ellipse that can inscribe the central cross-section of the particle, respectively.
[0060] The "diameter" d of the particle is the maximum dimension that can be observed along a line passing through the center of a circle or sphere.
[0061] Shape of the particle According to the present invention, bismuth oxycarbonate particles having the following empirical formula (BiO) 2-x (CO3) (where -0.4 < x < 0.6) can be in any form.
[0062] The shape of the particles will depend in particular on the method and operating conditions for preparing them.
[0063] In particular, the particles according to the present invention can be in the form of tubes, platelets, sheets, rods, spheres, flowers, pompoms, threads, filaments, fibers, needles, cubes, or any combination thereof.
[0064] Moreover, the particles according to the present invention can aggregate in the form of superstructures. For example, platelets, tubes and / or rods can aggregate in the form of spheres, flowers, or pompoms.
[0065] According to a preferred embodiment, the particles according to the present invention are in the form of tubes, platelets and / or rods. More preferably, the particles according to the present invention are in the form of platelets and / or rods.
[0066] Thus, particles in the form of plates or rods or tubes are specifically distinct from particles in the form of spheres or fibrous forms, flowers, pom-poms, threads, filaments, needles or cubes.
[0067] Of course, the particles according to the invention can be used in the form of a mixture, in particular the particles according to the invention can be used in any proportion of platelets and / or rods and / or tubes in the mixture.
[0068] According to one preferred embodiment, the particles used according to the invention are predominantly or exclusively of platelet morphology.
[0069] A particle in a "plate-like" morphology has a length that is greater than its width, and a width that is greater than its thickness.
[0070] In particular, when the particles are in platelet morphology, the particles according to the invention have: The average length L is in the range of 15 to 300 nm, particularly in the range of 30 to 250 nm, preferably in the range of 50 to 200 nm, and more preferably in the range of 70 to 150 nm; The average width l is in the range of 10 to 250 nm, particularly in the range of 20 to 200 nm, preferably in the range of 30 to 150 nm, and more preferably in the range of 50 to 120 nm; The average thickness e is in the range of 2 to 120 nm, particularly in the range of 5 to 100 nm, preferably in the range of 10 to 80 nm, and more preferably in the range of 20 to 50 nm; and e <l<Lである。
[0071] According to one preferred embodiment, the particles used according to the invention are predominantly or exclusively of rod-like morphology.
[0072] Particles in a "rod-like" morphology have a solid cylindrical morphology, where the length L of the particle is greater than the diameter d of the particle, or have a prismatic morphology, where the base of the particle is a solid polygon, preferably a triangle or hexagon, and the diameter d of the circle contained within the base of the polygon is less than the length L of the cylinder.
[0073] In particular, when the particles are rod-shaped, regardless of whether they are cylindrical or prismatic, the particles according to the invention have: The average length L is in the range of 30 to 300 nm, particularly in the range of 50 to 250 nm, preferably in the range of 70 to 230 nm, and more preferably in the range of 70 to 140 nm; the average diameter d is in the range of 15 to 150 nm, in particular in the range of 20 to 130 nm, preferably in the range of 25 to 120 nm, more preferably in the range of 25 to 100 nm, even more preferably in the range of 25 to 60 nm; and L>d.
[0074] According to one preferred embodiment, the particles used according to the invention are predominantly or exclusively of tubular morphology.
[0075] A particle in a "tubular" morphology has a hollow cylindrical shape, with the length L of the particle being greater than the diameter d of the particle.
[0076] In particular, when in tubular form, the particles according to the invention have: The average length L is in the range of 10 to 300 nm, particularly in the range of 20 to 250 nm, preferably in the range of 40 to 200 nm, and more preferably in the range of 60 to 200 nm; The average diameter d is in the range of 2 to 30 nm, particularly in the range of 3 to 20 nm, preferably in the range of 5 to 15 nm; and L>d.
[0077] For the purposes of the present invention, "predominantly platelet / rod / tubular morphology" is intended to indicate that at least 50% by number, in particular at least 70% by number, or even at least 90% by number, of the particles are of platelet / rod / tubular morphology, respectively.
[0078] Doping of the particles According to a particular embodiment, the bismuth oxycarbonate particles according to the invention can be doped.
[0079] In particular, the bismuth oxycarbonate particles according to the invention can be doped with one or more chemical elements capable of being inserted into the structure or of partially substituting elements already present.
[0080] The particles can be doped through substitution of all or part of the cations and / or all or part of the anions.
[0081] According to a particular embodiment, the doping is partial in terms of cations inserted or as substitutions for the bismuth, up to a limit of 20% of the composition in terms of bismuth.
[0082] According to this variant, the degree of doping varies in particular between 0.005% and 15%, preferably between 0.05% and 12%, better still between 0.1% and 10% and even better still between 0.5% and 6%.
[0083] In particular, the particles according to the invention can be doped with cations from elements selected from aluminum (symbol Al), silicon (symbol Si), scandium (symbol Sc), titanium (symbol Ti), vanadium (symbol V), manganese (symbol Mn), iron (symbol Fe), copper (symbol Cu), zinc (symbol Zn), gallium (symbol Ga), germanium (symbol Ge), yttrium (symbol Y), zirconium (symbol Zr), niobium (symbol Nb), molybdenum (symbol Mo), silver (symbol Ag), indium (symbol In), lanthanum (symbol La), cerium (symbol Ce), tantalum (symbol Ta), tungsten (symbol W) and / or gold (symbol Au).
[0084] Preferably, the particles according to the invention may be doped with cations derived from elements selected from titanium, vanadium, manganese, iron, copper, zinc, lanthanum and / or cerium atoms, more preferably selected from manganese, iron and / or cerium atoms, even more preferably selected from manganese or iron atoms.
[0085] According to a variant embodiment, the particles according to the invention are doped with cations derived from manganese, and the degree of doping varies in particular between 0.5% and 2%.
[0086] According to another variant embodiment, the particles according to the invention are doped with cations derived from iron, and the degree of doping varies in particular between 0.5% and 2%.
[0087] According to another particular embodiment, the doping is partial or total with respect to inserted anions or anions as substitutions of the carbonate groups, up to a limit of 20% of the composition with respect to carbonate.
[0088] According to this variant, the degree of doping varies in particular between 0.001% and 1%, preferably between 0.002% and 0.5%, better still between 0.003% and 0.2% and even better still between 0.005% and 0.1%.
[0089] In particular, the particles according to the invention are anions derived from elements selected from fluorine (symbol F), sulfur (symbol S), chlorine (symbol Cl), bromine (symbol Br) and iodine (symbol I) atoms, in particular sulfate (SO 2- ), sulfonate ion (S(=O)2-O - ), sulfite ion (SO3 2- ), phosphate ion (PO4 3- ) and / or iodate ion (IO3 - ) and can be doped.
[0090] Preferably, the particles according to the invention have the structure S 2- , SO3 2- , SO4 2-, Cl - And / or I - and more preferably SO3 2- , SO4 2- and / or Cl - and more preferably Cl - or SO4 2- So you can dope it.
[0091] According to a variant embodiment, the particles according to the invention are doped with anions derived from chlorine, and the degree of doping varies in particular between 0.01% and 0.1%.
[0092] According to another variant embodiment, the particles according to the invention are doped with anions derived from iodine, and the degree of doping varies in particular between 0.003% and 0.01%.
[0093] According to another variant embodiment, the particles according to the invention are doped with sulfate ions and the degree of doping varies in particular between 0.005% and 0.1%.
[0094] According to another variant embodiment, the particles according to the invention are doped with cations, preferably derived from elements selected from titanium, vanadium, manganese, iron, copper, zinc, lanthanum and / or cerium, more preferably from manganese, iron and / or cerium, even more preferably from manganese or iron, more preferably from manganese, iron and / or cerium, even more preferably from manganese or iron, and with anions, preferably derived from elements selected from fluorine (F), sulfur (S), chlorine (Cl), bromine (Br), iodine (I) and / or polyatomic anions, in particular sulfate ions (SO 2- ), sulfonate ion (S(=O)-O2 - ), sulfite ion (SO3 2- ), phosphate ion (PO4 3- ) and / or iodate ion (IO3 - ), more preferably S 2- , SO3 2- , SO42- , Cl - And / or I - , and more preferably SO3 2- , SO4 2- and / or Cl - , particularly preferably Cl - , I - or SO4 2- , and is doped with
[0095] According to a preferred embodiment, the bismuth oxycarbonate grains required according to the invention are undoped.
[0096] According to another preferred embodiment, the bismuth oxycarbonate particles required according to the invention are doped.
[0097] According to another preferred embodiment, the bismuth oxycarbonate particles required according to the invention are a mixture of doped and undoped particles.
[0098] Method for preparing said particles The bismuth oxycarbonate particles according to the invention may be obtained by any preparation method known to a person skilled in the art.
[0099] For example, the synthesis of bismuth oxycarbonate particles according to the present invention is described in the paper by Ni et al. (Fabrication, modification and application of (BiO)2CO3-based photocatalysts: A review, Applied Surface Science, 365, 2016, 314-335).
[0100] In particular, the particles according to the invention can be prepared by a solvothermal route, by an electrochemical route, by co-precipitation or else at reflux, preferably by a solvothermal route or at reflux.
[0101] According to a first variant embodiment, the particles according to the invention are obtained by the solvothermal route, in particular from bismuth nitrate and various carbonation agents, such as sodium carbonate, ammonium carbonate or urea, in a polar protic solvent in the presence of a polyol. Such a synthesis makes it possible to obtain bismuth oxycarbonate particles in the form of plates and / or rods, the maximum dimensions of which are between 50 and 300 nm.
[0102] The synthesis of such particles by solvothermal routes, in particular, Cheng, G. et al. (Shape-controlled solvothermal synthesis of bismuth subcarbonate nanomaterials, J. Solid State Chem. 183, 1878-1883 (2010)); Ruan, MM et al. (Facile Green Synthesis of Highly Monodisperse Bismuth Subcarbonate Micropompons Self-assembled by Nanosheets: Improved Photocatalytic Performance, Acta Physico-Chimica Sinica, 33, 2017, 1033-1042); Quin et al. (Template-Free Fabrication of Bi2O3 and (BiO)2CO3 Nanotubes and Their Application in Water Treatment, Chem. Eur. J., 18, 2012, 16491-16497); Cheng, G. et al. (Shape-controlled solvothermal synthesis of bismuth subcarbonate nanomaterials, J. Solid State Chem. 183, 1878-1883 (2010)); Chem., 183, 2010, 1878~1883); Liu, YY et al. (Preparation, electronic structure, and photocatalytic properties of Bi2O2CO3nanosheet, Appl.Surf.Sci.,257,2010,172~175); Zheng et al. (Synthetic Bi2O2CO3 nanostructures: Novel photocatalyst with controlled special surface exposed, Journal of Molecular Catalysis A: Chemical,2010,317 (1-2),34-40); Liu,SQ et al. (The effects of citrate ion on morphology and photocatalytic activity of flower-like Bi2O2CO3, Ceram.Int.,40,2014,2343~2348); or Chen,R. et al. (Bismuth subcarbonate nanoparticles fabricated by water-in-oil microemulsion-assisted hydrothermal process exhibit anti-Helicobacter pylori properties, Mater.Res.Bull.,45,2010,654~658).
[0103] The synthesis of said particles by an electrochemical route is described in particular in the article by Hu, Y. et al. (Simple hydrolysis route to synthesize Bi2O2CO3 nanoplate from Bi nanopowder and its photocatalytic application, Materials Letters, 170, 2016, 72-75).
[0104] The synthesis of such particles by coprecipitation is particularly described by Chen, XY et al. (Controlled synthesis of bismuth oxo nanoscale crystals (BiOCl,Bi 12 O 17Cl2, α-Bi2O3, and (BiO)2CO3) by solution-phase methods, J. Solid State Chem., 180, 2007, 2510-2516).
[0105] The synthesis of said particles by reflux is described in particular in the article by Chen et al. (Fabrication of bismuth subcarbonate nanotube arrays from bismuth citrate, Chem. Commun., 2006, 2265-2267).
[0106] According to a preferred embodiment, the bismuth oxycarbonate particles required according to the invention are obtained by a solvothermal route, for example according to the method described by Cheng et al., or at reflux, for example according to the method described by Chen et al.
[0107] According to a preferred embodiment, the bismuth oxycarbonate particles required according to the invention are obtained by a preparation process which uses one or more bismuth(III) complexes, one or more carbonation agents, one or more polyols and, optionally, one or more polar solvents other than said polyols.
[0108] When the particles used according to the invention are doped, one or more additional reagents containing a doping element may be added.
[0109] In particular, the one or more bismuth(III) complexes are selected from bismuth nitrate and its hydrates, bismuth citrate and its hydrates, bismuth sulfate and its hydrates, and bismuth chloride and its hydrates.
[0110] The one or more bismuth(III) complexes may also be derived from bismuth minerals, such as elemental bismuth and / or bismuth oxide and / or bismuth sulfide.
[0111] Preferably, the one or more bismuth(III) complexes are bismuth(III) nitrate and its hydrates of the formula Bi(NO3)3·xH2O, preferably bismuth nitrate pentahydrate of the formula Bi(NO3)3·5H2O.
[0112] In particular, the one or more carbonation agents are selected from Li2CO3, Na2CO3, K2CO3, Rb2CO3, Cs2CO3, (NH4)2CO3, LiHCO3, NaHCO3, KHCO3, RbHCO3, CsHCO3, (NH4)HCO3, urea (NH2)2CO and urea derivatives, CO2, preferably selected from Na2CO3, K2CO3, (NH2)2CO, (NH4)2CO3, more preferably selected from (NH2)2CO and / or (NH4)2CO3.
[0113] A polyol is a compound having multiple hydroxyl functional groups. The polyol may be selected in particular from glycols, in particular ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, hexylene glycol; short- or long-chain glycol polymers, such as polyethylene glycol, polypropylene glycol, polybutylene glycol; glycerol and its derivatives; or, for example, sugars, in particular glucose, fructose, sucrose, xylitol, mannitol, such as D-mannitol, sorbitol or maltitol.
[0114] According to one embodiment, the bismuth oxycarbonate particles required according to the invention are obtained by a preparation process using a polyol, or a mixture of polyols.
[0115] According to a first variant embodiment, one or more polyols may also be used as solvent.The particles according to the invention can then be obtained, for example, according to the method described below.
[0116] Solution A is formed from dissolving the bismuth(III) complex in a polyol or mixture of polyols, preferably at a concentration of 0.001 to 0.5 M. Solution B is formed by partially or completely dissolving a carbonation agent, preferably 1 to 100 equivalents of carbonation agent relative to the bismuth, in the polyol or mixture of polyols, or in a polyol or mixture of polyols other than the polyol (or mixture of polyols) used in solution A.
[0117] In the case of doping with cations, the dopant is preferably incorporated in solution A. In the case of doping with anions, the dopant is preferably incorporated in solution B.
[0118] In the case of doping with one or more cations and / or one or more anions, the one or more cationic dopants are preferably incorporated in solution A and the anionic dopants are preferably incorporated in solution B. Subsequently, solution A is added to solution B. If the polyol or mixture of polyols is not liquid at ambient temperature, all solids are mixed.
[0119] The resulting mixture is then heated at 90-250° C. for a reaction time of 10 minutes to 48 hours. If the desired reaction temperature is equal to or higher than the boiling point of the solvent, the solvothermal synthesis is carried out using an autoclave.
[0120] Preferably, the reaction temperature is 95° C. to 200° C. and the reaction time is 1 hour to 24 hours, and more preferably, the reaction temperature is 100° C. to 180° C. and the reaction time is 2 hours to 16 hours.
[0121] The resulting particles are separated from the reaction medium by centrifugation and washed by successive cycles of dispersion and centrifugation.
[0122] After drying under vacuum at temperatures between 40°C and 60°C, a white powder is obtained.
[0123] When one or more polyols are used as solvent, the bismuth oxycarbonate particles according to the invention obtained are of platelet morphology, preferably with an average thickness e between 2 and 15 nm, and / or of tubular morphology.
[0124] According to another variant embodiment, the one or more polyols are used only as additives and not as solvents.The particles according to the invention can then be obtained, for example according to the method described below.
[0125] Solution A is formed by dissolving in a solvent, preferably a polar solvent, a bismuth complex, preferably at a concentration of 0.001-0.5 M, and one or more polyols, preferably at a total polyol concentration of 0.01-5 M. Solution B is formed by partially or completely dissolving a carbonation agent, preferably 1-100 equivalents of carbonation agent relative to the bismuth complex, in a polar solvent (miscible with the solvent from solution A) that is the same or different (preferably the same) as the solvent of solution A.
[0126] In the case of doping with cations, the dopant is preferably incorporated in solution A. In the case of doping with anions, the dopant is preferably incorporated in solution B.
[0127] In the case of doping with one or more cations and / or one or more anions, the one or more cationic dopants are preferably incorporated in solution A and the one or more anionic dopants are preferably incorporated in solution B.
[0128] Solution A is then added to solution B at ambient temperature. The resulting mixture is then heated at 90° C. to 250° C. for 10 minutes to 48 hours. If the desired reaction temperature is above the boiling point of the solvent, the solvothermal synthesis is carried out using an autoclave.
[0129] Preferably, the reaction temperature is 90° C. to 150° C., and the reaction time is 4 hours to 16 hours.
[0130] The resulting particles are separated from the reaction medium by centrifugation and washed by successive cycles of dispersion and centrifugation.
[0131] After drying under vacuum at temperatures between 40°C and 60°C, a white powder is obtained.
[0132] When the one or more polyols are used only as additives, they may in particular be chosen from ethylene glycol, propylene glycol, glycerol and / or sugars, preferably sugars, more preferably D-mannitol.
[0133] According to this variant, the synthesis method uses a solvent other than the polyol or a mixture of solvents other than the polyol, in particular the solvent or mixture of solvents is selected from polar solvents, preferably polar and protic solvents, such as water, C1-C6 alcohols, such as ethanol or isopropanol, and combinations thereof, and more preferably still water.
[0134] In particular, when one or more polyols are selected as the only additive and water is selected as the solvent, the bismuth oxycarbonate particles according to the invention are preferably obtained in the form of plates and / or rods.
[0135] Cosmetic Composition The bismuth oxycarbonate particles according to the invention may in particular be used in compositions, in particular cosmetic compositions.
[0136] The present invention therefore also relates to a composition, in particular a cosmetic composition, comprising i) bismuth oxycarbonate particles as defined above; ii) at least one aqueous phase and / or at least one fatty phase; and iii) at least one compound selected from a) a UV screening agent other than said bismuth oxycarbonate particles i); b) a colorant; c) a cosmetic active agent for caring for keratinous materials; d) a surfactant; e) a thickener; and combinations thereof. The present invention relates to a composition, particularly a cosmetic composition, comprising at least one of the above.
[0137] The bismuth oxycarbonate particles may be present in the composition, preferably in the cosmetic composition, in a content ranging from 0.5% to 40% by weight, preferably from 1% to 30% by weight and even better still from 2% to 20% by weight, relative to the total weight of the composition.
[0138] aqueous phase The compositions according to the invention, in particular cosmetic compositions, may comprise at least one aqueous phase.
[0139] The aqueous phase may comprise water and, optionally, a water-soluble solvent.
[0140] In the present invention, the term "water-soluble solvent" refers to a compound which is liquid at ambient temperature and which is water-miscible (50% by weight or more miscible in water at 25° C. and atmospheric pressure).
[0141] The water-soluble solvents that can be used in the compositions according to the invention can furthermore be volatile.
[0142] Among the water-soluble solvents that may be used in the compositions according to the invention, lower monoalcohols having 1 to 5 carbon atoms, such as ethanol and isopropanol, C2-C 32 Polyols, C3 and C4 ketones and C2 to C4 aldehydes may especially be mentioned.
[0143] For purposes of this invention, "polyol" means any organic molecule that contains at least two free hydroxyl groups.
[0144] Polyols suitable for the present invention can be saturated or unsaturated, linear, branched or cyclic alkyl-type compounds having at least two -OH functional groups on the alkyl chain, particularly at least three -OH functional groups, more particularly at least four -OH functional groups.
[0145] Polyols which are advantageously suitable for formulating the compositions according to the invention are especially those which contain from 2 to 32 carbon atoms, preferably from 3 to 16 carbon atoms.
[0146] Advantageously, the polyol may be chosen, for example, from pentaerythritol, trimethylolpropane, caprylyl glycol, glycerol, polyglycerols, such as glycerol oligomers, such as diglycerol, and polyethylene glycol, and combinations thereof.
[0147] In particular, the composition according to the invention may comprise from 5% to 80% by weight, preferably from 20% to 60% by weight, of aqueous phase relative to the total weight of the composition.
[0148] fat phase The compositions according to the invention, in particular cosmetic compositions, may further comprise at least one fatty phase, in particular an oily phase.
[0149] For the purposes of the present invention, "fatty phase" means a phase comprising at least one fatty substance and all of the fat-soluble and lipophilic components used for the formulation of the composition of the invention.
[0150] Preferably, the fatty phase comprises at least one oil, in particular a cosmetic oil.
[0151] The term "oil" means a water-immiscible, non-aqueous compound that is liquid at room temperature (25° C.) and atmospheric pressure (760 mmHg).
[0152] The fatty phase may comprise at least one volatile or non-volatile hydrocarbon-based oil and / or fatty substance, preferably a volatile and / or non-volatile silicone oil and / or a volatile and / or non-volatile fluoro oil.
[0153] Non-volatile hydrocarbon oils include hydrocarbon oils of vegetable origin, synthetic ethers having 10 to 40 carbon atoms, linear or branched hydrocarbons of mineral or synthetic origin, synthetic esters, fatty alcohols which are liquid at room temperature and have branched and / or unsaturated carbon chains having 12 to 26 carbon atoms, C 12 ~C 22 Particular mention may be made of higher fatty acids, carbonates, and combinations thereof.
[0154] As volatile hydrocarbon-based oils, mention may in particular be made of hydrocarbon-based oils having a number of carbon atoms ranging from 8 to 16.
[0155] The non-volatile silicone oils may in particular be chosen from non-volatile polydimethylsiloxanes (PDMS) and phenylated silicones. As volatile silicone oils, mention may be made, for example, of volatile linear or cyclic silicone oils.
[0156] Volatile fluoro oils such as nonafluoromethoxybutane, decafluoropentane, tetradecafluorohexane, dodecafluoropentane, and combinations thereof may also be used.
[0157] The oil phase may further comprise other fatty substances mixed with the oil or dissolved in the oil. The other fatty substances that may be present in the oil phase may be, for example, fatty acids, waxes, gums, pasty compounds, or combinations thereof.
[0158] a) UV screening agent According to a particular embodiment, the composition according to the invention comprises a) at least one UV screening agent other than the bismuth oxycarbonate particles required according to the invention and defined above.
[0159] For the purposes of the present invention, "UV screening agent other than bismuth oxycarbonate particles" is intended to denote any UV screening agent whose chemical properties are required according to the present invention and which are different from bismuth oxycarbonate particles as defined above.
[0160] Thus, the bismuth oxycarbonate particles according to the invention can be used alone or in combination with a) other UV screening agents, in particular selected from organic and / or inorganic UV screening agents.
[0161] Thus, the cosmetic composition may comprise one or more additional UV screening agents selected from hydrophilic, lipophilic or insoluble organic UV screening agents and / or mineral UV screening agents.
[0162] By "hydrophilic UV screening agent" is meant any cosmetic or dermatological organic or inorganic compound for filtering UV radiation, which is capable of being completely dissolved in molecular form in an aqueous liquid or else of being present in colloidal suspension (e.g. in micellar form) in an aqueous liquid.
[0163] By "lipophilic UV screening agent" is meant any cosmetic or dermatological organic or inorganic compound for filtering UV radiation, said organic or inorganic compound being capable of being completely dissolved in molecular form in a liquid fatty phase or else being present in colloidal suspension (for example in micellar form) in a liquid fatty phase.
[0164] "Insoluble UV screening agents" are any cosmetic or dermatological organic or inorganic compounds for filtering UV radiation, which have a solubility in water of less than 0.5% by weight, and which are insoluble in most organic solvents, such as liquid paraffin, fatty alcohol benzoic acid esters and fatty acid triglycerides, e.g. Miglyol 812 sold by Dynamit Nobel. 登録商標means the above organic or inorganic compounds having a solubility in the solvent of less than 0.5% by weight, measured at 70° C. and defined as the amount of product in solution in the solvent that is in equilibrium with the excess solid in suspension after being returned to ambient temperature. It can be easily evaluated in the laboratory.
[0165] The additional organic UV screening agents are in particular selected from: Cinnamic compounds, especially ethylhexyl methoxycinnamate, Anthranilic acid compounds, in particular menthyl anthranilate; Salicylates, especially homosalate and ethylhexyl salicylate; Dibenzoylmethane compounds, in particular butyl methoxydibenzoylmethane; Benzylidene camphor compounds, in particular 3-benzylidene camphor, 4-methylbenzylidene camphor, benzylidene camphorsulfonic acid, and terephthalylidene dicamphorsulfonic acid; Benzophenone compounds, in particular oxybenzone and n-hexyl 2-(4-diethylamino-2-hydroxybenzoyl)benzoate; β,β-diphenylacrylate compounds, especially octocrylene, Triazine compounds, in particular phenylenebisdiphenyltriazine, bisethylhexyloxyphenolmethoxyphenyltriazine, ethylhexyl triazone, and diethylhexylbutamidotriazine; Benzotriazole compounds, in particular drometrizole trisiloxane, Benzalmalonate compounds, in particular those compounds mentioned in US Pat. No. 5,624,663, in particular Polysilicone-15; Benzimidazole derivatives, in particular phenylbenzimidazole sulfonic acid, Imidazoline compounds, in particular dimethoxybenzylidene dioxoimidazoline ethylhexyl propionate, Bisbenzoazolyl compounds, such as those described in European Patent No. EP 0 669 323 and US Pat. No. 2,463,264, in particular disodium phenyldibenzimidazole tetrasulfonate; para-aminobenzoic acid compounds, particularly PABA, ethylhexyl dimethyl PABA, and PEG-25 PABA; Methylene bis(hydroxyphenylbenzotriazole) compounds, such as those described in U.S. Pat. Nos. 5,237,071, 5,166,355, GB 2,303,549, DE 19726,184, and EP 0,893,119, in particular methylene bisbenzotriazolyl tetramethylbutylphenol; Benzoxazole compounds, such as those described in EP 0832642, EP 1027883, EP 1300137 and DE 10162844, in particular 2,4-bis-[5-1(dimethylpropyl)benzoxazol-2-yl-(4-phenyl)-imino]-6-(2-ethylhexyl)-imino-1,3,5 triazine, Polymer screening agents and silicone screening agents, such as, in particular, those compounds described in International Publication WO 93 / 04665; Dimers derived from α-alkylstyrenes, for example dimers as described in German Patent DE 19855649; 4,4-diarylbutadiene compounds, such as those described in EP 0 967 200, DE 19746 654, DE 19755 649, EP 1 008 586, EP 1 133 980 and EP 0 133 981, in particular 1,1-dicarboxy(2,2′-dimethylpropyl)-4,4-diphenylbutadiene, and A combination of them.
[0166] The inorganic UV screening agents are generally mineral UV screening agents, in particular selected from metal oxides.
[0167] The metal oxide may in particular be chosen from titanium oxide, zinc oxide, iron oxide, zirconium oxide, cerium oxide, and combinations thereof.
[0168] The metal oxide particles may be coated or uncoated.
[0169] The coated particles are more particularly titanium oxide particles coated with silica, titanium oxide particles coated with silica and iron oxide, titanium oxide particles coated with silica and alumina, titanium oxide particles coated with alumina, titanium oxide particles coated with alumina and aluminum stearate, titanium oxide particles coated with silica, alumina and alginic acid, titanium oxide particles coated with alumina and aluminum laurate, titanium oxide particles coated with iron oxide and iron stearate, titanium oxide particles coated with zinc oxide and zinc stearate, titanium oxide particles coated with silica and alumina and treated with silicone, titanium oxide particles coated with silica and treated with silicone, titanium oxide particles treated with silica, titanium oxide particles treated with alumina, aluminum stearate. and silicone-treated titanium oxide particles, titanium oxide particles coated with silica and silicone-treated titanium oxide particles, titanium oxide particles treated with alumina and silicone-treated titanium oxide particles, titanium oxide particles coated with triethanolamine, titanium oxide particles coated with stearic acid, titanium oxide particles coated with sodium hexametaphosphate, or otherwise TiO2 treated with octyltrimethylsilane, TiO2 treated with polydimethylsiloxane, anatase / rutile TiO2 treated with polydimethylhydrosiloxane, TiO2 coated with triethylhexanoin, aluminum stearate and alumina, TiO2 coated with aluminum stearate, TiO2 coated with alumina and silicone-treated TiO2, TiO2 coated with lauroyl lysine, or C. 9~15 It is TiO2 coated with fluoroalcohol phosphate and aluminum hydroxide.
[0170] The metal oxide may optionally be doped.
[0171] In this respect, mention may be made of TiO2 particles doped with at least one transition metal, such as iron, zinc or manganese, in particular manganese.
[0172] The doped particles may be in the form of a dispersion, preferably an oil dispersion. The oil present in the oil dispersion is preferably selected from triglycerides, including capric / caprylic triglycerides. The oil dispersion of titanium dioxide particles may additionally contain one or more dispersants, such as sorbitan esters or polyoxyalkylenated glycerol fatty acid esters. Particular mention may be made of an oil dispersion of manganese-doped TiO2 particles in capric / caprylic triglycerides in the presence of tri-PPG-3-myristyl ether citrate and polyglyceryl-3-polyricinoleate and sorbitan isostearate.
[0173] Mixtures of metal oxides may also be mentioned, in particular mixtures of titanium dioxide and cerium dioxide, including equal weight mixtures of titanium dioxide and cerium dioxide coated with silica, and also mixtures of titanium dioxide and zinc dioxide coated with alumina, silica and silicone, or coated with alumina, silica and glycerol.
[0174] b) Colorants According to a particular embodiment, the composition according to the invention comprises b) at least one colorant.
[0175] In general, "colorant" is intended to denote any compound capable of coloring a composition, i.e., any compound that absorbs in the visible spectrum, in particular any compound that absorbs in the visible spectrum so as to be visible to the human eye as having a color, e.g., yellow, orange, red, purple, blue or green.
[0176] Preferably, the composition according to the invention comprises at least one pigment.
[0177] "Pigments" should be understood as meaning white or colored mineral or organic particles that are insoluble in liquid lipophilic and hydrophilic phases and are intended to color and / or opacify the compositions that contain them. More particularly, the pigments are poorly or not at all soluble in aqueous-alcoholic media.
[0178] Pigments that may be used are in particular selected from organic and / or mineral pigments known in the art, in particular the pigments described in Kirk-Othmer's Encyclopedia of Chemical Technology and in Ullmann's Encyclopedia of Industrial Chemistry (Ullmann's Encyclopedia of Industrial Chemistry "Pigment organics", 2005 Wiley-VCH Verlag GmbH & Co.KGaA, Weinheim 10.1002 / 14356007.a20 371 and ibid, "Pigments, Inorganic, 1. General" 2009 Wiley-VCH Verlag GmbH & Co.KGaA, Weinheim10.1002 / 14356007.a20_243.pub3).
[0179] These pigments are in the form of a pigment powder or a paste. The pigments may be coated or uncoated.
[0180] The pigments may be selected, for example, from mineral pigments, organic pigments, lakes, special effect pigments such as nacres or glitter flakes, and combinations thereof.
[0181] The pigment may be a mineral pigment. The term "mineral pigment" refers to a pigment that meets the definition in the chapter on inorganic pigments in Ullmann's Encyclopedia. Among the mineral pigments that are useful in the present invention, mention may be made of iron oxide, chromium oxide, manganese violet, ultramarine blue, chromium hydrate, ferric blue and titanium oxide.
[0182] The pigment may be an organic pigment.
[0183] The term "organic pigment" refers to pigments that meet the definition in the Ullmann Encyclopedia chapter on organic pigments.
[0184] The organic pigments may in particular be chosen from nitroso, nitro, azo, xanthene, quinoline, anthraquinone, metal complex type phthalocyanines, isoindolinone, isoindoline, quinacridone, perinone, perylene, diketopyrrolopyrrole, thioindigo, dioxazine, triphenylmethane or quinophthalone compounds.
[0185] Preferably, the one or more pigments suitable for the present invention are carbon black, iron oxides, in particular red, brown or black iron oxides, and mica coated with iron oxide, triarylmethane pigments, in particular blue and purple triarylmethane pigments, such as BLUE 1 LAKE, azo pigments, in particular red azo pigments, such as D&C RED 7, alkali metal salts of lithol red, such as the calcium salt of lithol red B; more preferably, the one or more pigments used are selected from red iron oxides and azo pigments, in particular red azo pigments, such as D&C RED 7.
[0186] The one or more colorants may be present in the composition according to the invention in a content ranging from 0.001% to 10% by weight, and preferably from 0.005% to 5% by weight, relative to the total weight of the composition.
[0187] According to a particular embodiment of the invention, the amount of pigments varies from 0.5% to 40%, and preferably from 1% to 20%, relative to the weight of the composition according to the invention that contains them.
[0188] c) Cosmetic active agents According to a particular embodiment, the composition according to the invention comprises c) at least one cosmetic active agent for caring for keratinous materials, preferably for caring for the skin.
[0189] In particular, the cosmetic active agent may be at least one hydrophilic active agent and / or one lipophilic active agent, preferably one lipophilic active agent that is hydrophilic.
[0190] "Hydrophilic active" means a water-soluble or water-dispersible active capable of forming hydrogen bonds.
[0191] Among the cosmetic active agents there may be mentioned, for example, moisturizers, depigmenting agents, desquamating agents, moisturizers, anti-aging agents, mattifying agents, cicatrizing agents, antibacterial agents, vitamins and their derivatives or precursors, antioxidants, sunscreens, free radical scavengers, anti-pollution agents, self-tanning agents, anti-glycation agents, soothing agents, deodorants, essential oils, NO synthase inhibitors; agents stimulating the synthesis and / or preventing the degradation of dermal or epidermal macromolecules; agents stimulating the proliferation of fibroblasts; agents stimulating the proliferation of keratinocytes; muscle relaxants; refreshing agents; tonicity agents; pigmentation promoters; keratolytic agents; hair thinning agents; agents acting on the energy metabolism of cells; insect repellents; substance P or CRGP antagonists; agents preventing hair loss; and combinations thereof.
[0192] The one or more active agents may in particular be selected from: Vitamins and their derivatives, especially their esters, such as niacinamide (3-pyridinecarboxamide), nicotinamide (vitamin B3), tocopherol (vitamin E) and its esters (e.g. tocopherol acetate), ascorbic acid and its derivatives (vitamin C), retinol (vitamin A), Humectants or moisturizers, such as urea, hydroxyurea, glycerol, polyglycerol, glyceryl glucoside, diglyceryl glucoside, polyglyceryl glucoside, xylyl glucoside and plant extracts (especially tea, mint, orchid, soy, aloe vera, honey), and especially glycerol; C-glycoside compounds, preferably hydroxypropyltetrahydropyrantriol (or proxylane); Antioxidant compounds; Anti-ageing active agents, such as hyaluronic acid compounds, in particular sodium hyaluronate, salicylic acid compounds, in particular 5-n-octanoylsalicylic acid (capryloylsalicylic acid), adenosine, C-β-D-xylopyranoside-2-hydroxypropane and the sodium salt of (3-hydroxy-2-pentylcyclopentyl)acetic acid; Keratolytic agents, such as lactic acid and glycolic acid; and A combination of them.
[0193] Such active agents may be present in the composition according to the invention in a content ranging from 0.05% to 10% by weight, and preferably from 1.0% to 8.0% by weight, relative to the total weight of the composition.
[0194] d) Surfactants According to a particular embodiment, the composition according to the invention comprises d) at least one surfactant.
[0195] The surfactant may be selected from nonionic surfactants, anionic surfactants, cationic surfactants and amphoteric surfactants, and combinations thereof. Definitions of the emulsifying properties and functions of surfactants are found in Kirk-Othmer Encyclopedia of Chemical Technology, volume 22, pages 333-432, 3 rd Edition, 1979, Wiley, in particular pages 347-377 of this document regarding anionic surfactants, amphoteric surfactants and nonionic surfactants.
[0196] Examples of amphoteric surfactants which are suitable for the present invention are in particular betaines, preferably selected from alkyl betaines, in particular lauryl betaine, N-alkylamido betaines and derivatives thereof, in particular cocamidopropyl betaine, lauramidopropyl betaine and N-disodium N-carboxyethoxyethyl N-cocoylamidoethyl aminoacetate; sultaines, in particular cocoylamidopropyl hydroxysultaine; and combinations thereof thereof.
[0197] Nonionic surfactants may in particular be selected from alkyl and polyalkyl esters of poly(ethylene oxide), oxyalkylenated alcohols, alkyl and polyalkyl ethers of poly(ethylene oxide), optionally polyoxyethylenated alkyl and polyalkyl esters of sorbitan, optionally polyoxyethylenated alkyl and polyalkyl ethers of sorbitan, in particular alkyl and polyalkyl esters of sucrose, optionally polyoxyethylenated alkyl and polyalkyl esters of glycerol and optionally polyoxyethylenated alkyl and polyalkyl ethers of glycerol, gemini surfactants, cetyl alcohol, stearyl alcohol, and combinations thereof.
[0198] Anionic surfactants include alkyl ether sulfates, carboxylates, amino acid derivatives, sulfonates, isethionates, taurates, sulfosuccinates, alkyl sulfoacetates, phosphates and alkyl phosphates, polypeptides, C 10 ~C 30 , especially C 16 ~C 25 , metal salts of fatty acids, particularly metal stearates and behenates, and combinations thereof.
[0199] Cationic surfactants include alkyl imidazolidinium, such as isostearyl ethylimidonium ethosulfate; ammonium salts, such as (C 12~30 -alkyl)-tri(C 1~4- alkyl)ammonium halides, such as N,N,N-trimethyl-1-docosanaminium chloride (or behentrimonium chloride).
[0200] The silicone surfactant may be selected from a dimethicone copolyol or a silicone elastomer.
[0201] The composition according to the present invention may contain from 0.01% to 2.0% by weight, preferably from 0.05% to 1.5% by weight, and more preferably from 0.1% to 1.0% by weight of a surfactant, based on the total weight of the composition.
[0202] e) Thickeners According to a particular embodiment, the composition according to the invention comprises e) at least one thickening agent (also referred to as gelling agent or viscosity modifier).
[0203] The thickening agents may be synthetic, natural or naturally derived, preferably natural or naturally derived.
[0204] Such thickening agents may in particular be chosen from natural polymers or polymers of natural origin, in particular polymers of vegetable origin.
[0205] These gelling agents are preferably hydrophilic, ie, soluble or dispersible in water.
[0206] Advantageously, the one or more thickening agents are modified or natural polysaccharides, in particular modified or unmodified starch, fructans, gellan, glucans, amylose, amylopectin, glycogen, pullulan, dextran, cellulose and its derivatives, in particular methylcellulose, hydroxyalkylcellulose, ethylhydroxyethylcellulose and carboxymethylcellulose, mannans, xylans, lignins, araban, galactans, galacturonans, alginic acid compounds, chitin, chitosan, glucuronoxylan, arabinoxylan, xyloglucan, glucomannan, pectic acid and pectin, arabinogalactans, carrageenans, agar, glycosaminoglucans, gum arabic, sclerotium gum, glyceryl stearate ... The gums are selected from gum tragacanth, gum ghatti, gum karaya, locust bean gum, konjac gum, galactomannans such as guar gum and its non-ionic derivatives, in particular hydroxypropyl guar and its ionic derivatives, biopolysaccharide gums of microbial origin, in particular scleroglucan or xanthan gum, mucopolysaccharides, carboxyvinyl polymers, polyacrylamides, polymers and copolymers of 2-acrylamido-2-methylpropanesulfonic acid, water-soluble or water-dispersible silicone derivatives, optionally crosslinked and / or neutralized, such as acrylic silicones, polyether silicones and cationic silicones, and combinations thereof.
[0207] The one or more thickeners may be present in the composition according to the invention in a content ranging from 0.05% to 5.0% by weight, in particular from 0.3% to 4.0% by weight and more particularly from 0.4% to 2.5% by weight, relative to the total weight of the composition.
[0208] Adjuvants In addition, the composition according to the invention may contain at least one adjuvant conventional in the cosmetic field, said adjuvants being selected from fragrances, film-forming polymers, pH adjusters (acids or bases), such as citric acid, tartaric acid or oxalic acid, chelating agents, preservatives, emollients, sweeteners, antifoaming agents, fillers, trace elements, propellants, and combinations thereof.
[0209] Of course, the skilled artisan will take care to select this compound or any of these additional one or more compounds, and / or the amount thereof, such that the advantageous properties of the compositions according to the invention are not adversely affected or substantially not adversely affected by the envisaged addition.
[0210] Of course, one skilled in the art will take care to select this compound or any of these additional one or more compounds, and / or the amount thereof, such that the advantageous properties of the particles according to the invention are not adversely affected or are not substantially adversely affected by the envisaged addition.
[0211] As mentioned above, the composition according to the invention may be a cosmetic product, and preferably is a cosmetic product.
[0212] The compositions according to the invention are generally suitable for topical application to the skin and therefore generally comprise a physiologically acceptable medium, ie a medium that is compatible with the skin.
[0213] Preferably, the medium is cosmetically acceptable, i.e., has a pleasant color, odor and feel and does not cause unacceptable discomfort, i.e., tingling or tightness, that would discourage the user from applying the composition.
[0214] Presentation form of the composition Compositions, in particular cosmetic compositions, containing the particles according to the invention may be prepared according to techniques well known to those skilled in the art.
[0215] The compositions may be in any conventional presentation form, depending on the targeted application, and are suitable for topical application, ie application to the surface of the keratinous materials.
[0216] The cosmetic composition may be in the form of an aqueous or aqueous-alcoholic gel.
[0217] The composition may be in the form of a simple or multiple (O / W, W / O, O / W / O or W / O / W) emulsion, for example a cream, a milk or a gel-cream.
[0218] The composition may also be in anhydrous form, for example in the form of an oil.
[0219] "Anhydrous composition" means a composition comprising less than 5% by weight of water, or else less than 2% by weight of water, even better less than 1% by weight of water, in particular no water, wherein the water is not added during the preparation of the composition and corresponds to the residual water provided by the mixed ingredients.
[0220] The cosmetic composition may be used, for example, as a makeup product.
[0221] The cosmetic composition may be used as a care and / or sun protection product for the face and / or body, for example with a liquid to semi-liquid consistency and with the appearance of a relatively thick white or colored cream, pomade, milk, gel cream, lotion, serum, paste or mousse. Optionally, it may be applied to the skin in the form of an aerosol. The cosmetic composition may also be in solid form, for example in the form of a stick.
[0222] The cosmetic composition may be in the form of a product for caring for the skin or semi-mucous membranes, for example a protective or cosmetic care composition for the face, lips, hands, feet, anatomical folds or body (for example a day cream, night cream, day serum, night serum, makeup-removing cream, makeup base, protective or caring body milk, aftersun milk, a lotion, gel or foam for skin care or scalp care, a serum, a mask or an aftershave composition).
[0223] The composition may be applied by hand or with the use of an applicator.
[0224] In particular, the cosmetic composition has an SPF of greater than 5, preferably greater than 10.
[0225] "SPF", or "sun protection factor", measures the level of protection against UV rays. It is mathematically expressed by the ratio of the amount of UV radiation required to reach the erythema threshold with an anti-UV screening agent to the amount of UV radiation required to reach the erythema threshold without an anti-UV screening agent. Thus, the higher the SPF of a composition, the higher the anti-sun protection provided by this composition. More specifically, the term "SPF" is defined in the article "A new substrate to measure sunscreen protection factors throughout the ultraviolet spectrum, J. Soc. Cosmet. Chem., 40, 127-133 (May / June 1989)".
[0226] In particular, the cosmetic composition also has a PPD of greater than 3, preferably greater than 7.
[0227] "PPD" (Persistent Pigment Darkening) is an index that characterizes protection from UVA rays. In particular, the PPD measures the color of the skin observed 2 to 4 hours after exposure to UVA rays. This method has been used by the Japan Cosmetic Industry Association (JCIA) since 1996 as the official test method for UVA labeling of products, and is frequently used by European and American testing institutes (Technical Information of the Japan Cosmetic Industry Association, Measurement Standard for UV-A Protection Efficacy, January 1, 1996).
[0228] Cosmetic Uses and Methods The present invention also relates to a non-therapeutic cosmetic method for filtering UV irradiation, in particular UVB irradiation, which comprises at least administering to a keratinous material a composition comprising the bismuth oxycarbonate particles as defined above.
[0229] According to another of its aspects, the present invention also relates to the non-therapeutic cosmetic use of a cosmetic composition comprising the bismuth oxycarbonate particles as defined above for preventing the appearance of darker and / or more numerous and denser spots on the skin, in particular on the face, neckline, arms, hands and / or shoulders, which give the skin a non-uniform color.
[0230] The present invention also relates to a non-therapeutic cosmetic method for suppressing skin darkening and / or for improving the color and / or uniformity of the complexion, which comprises administering to the surface of a keratinous material at least one cosmetic composition comprising the bismuth oxycarbonate particles as defined above.
[0231] In addition, the present invention relates to the non-therapeutic cosmetic use of a cosmetic composition comprising the bismuth oxycarbonate particles as defined above for preventing premature aging of the skin, in particular of the face, neckline, arms, hands and / or shoulders.
[0232] The present invention also relates to a non-therapeutic cosmetic method for preventing and / or treating signs of aging of a keratinous material, which comprises administering to the surface of the keratinous material at least one cosmetic composition comprising the bismuth oxycarbonate particles as defined above.
[0233] According to one of its aspects, the present invention relates to bismuth oxycarbonate particles having the following empirical formula (BiO) 2-x (CO3) (wherein -0.4 < x < 0.6) for use as an agent for filtering UV irradiation, in particular UVB irradiation, said bismuth oxycarbonate particles having a maximum average dimension of less than 400 nm.
[0234] For the purposes of the present invention, "prevent" or "prevention" means at least partially reducing the risk of the occurrence of a given phenomenon, such as the signs of aging of keratinous materials or the appearance on the skin of darker and / or more pigmented spots that give the skin an uneven color, and / or the above-mentioned phenomena that result in premature aging of the skin.
[0235] In the specification and examples, percentages are percentages by weight. The ingredients are mixed in an order and under conditions that can be readily determined by one skilled in the art.
[0236] The invention will now be illustrated by the following examples which, of course, are given as non-limiting illustrations of the invention. [Brief description of the drawings]
[0237] [Figure 1] FIG. 1 illustrates an electron microscope photograph of bismuth oxycarbonate particles A. [Diagram 2] FIG. 2 illustrates an electron microscope photograph of bismuth oxycarbonate particles B. [Diagram 3] FIG. 3 illustrates an electron microscope photograph of bismuth oxycarbonate particles C. [Figure 4] FIG. 4 illustrates an electron microscope photograph of bismuth oxycarbonate particle D. [Diagram 5] FIG. 5 illustrates an electron microscope photograph of bismuth oxycarbonate particles E. [Figure 6] FIG. 6 illustrates an electron microscope photograph of bismuth oxycarbonate particles F. [Figure 7] FIG. 7 illustrates an electron microscope photograph of bismuth oxycarbonate particles G. [Figure 8] FIG. 8 illustrates an electron microscope photograph of bismuth oxycarbonate particles G′. [Figure 9] FIG. 9 illustrates an electron microscope photograph of bismuth oxycarbonate particles H. [Figure 10] FIG. 10 illustrates an electron microscope photograph of bismuth oxycarbonate particles H′. [Figure 11]FIG. 11 illustrates an electron micrograph of bismuth oxycarbonate particles I. [Figure 12] FIG. 12 illustrates an electron micrograph of bismuth oxycarbonate particle J. [Figure 13] FIG. 13 illustrates an electron microscope photograph of bismuth oxycarbonate particles K. [Figure 14] FIG. 14 illustrates an electron microscope photograph of bismuth oxycarbonate particles L. [Figure 15] FIG. 15 illustrates an electron microscope photograph of bismuth oxycarbonate particles M. [Figure 16] Figure 16 illustrates the UV-visible absorption spectra of product A and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 17] Figure 17 illustrates the UV-visible absorption spectra of product B and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 18] Figure 18 illustrates the UV-visible absorption spectra of product C and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 19] Figure 19 illustrates the UV-visible absorption spectra of product D and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 20]Figure 20 illustrates the UV-visible absorption spectra of product E and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 21] Figure 21 illustrates the UV-visible absorption spectra of product F and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 22] Figure 22 illustrates the UV-visible absorption spectra of product G and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 23] Figure 23 illustrates the UV-visible absorption spectra of product G' and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 24] Figure 24 illustrates the UV-visible absorption spectra of product H and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Diagram 25] Figure 25 illustrates the UV-visible absorption spectra of product H' and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 26]Figure 26 illustrates the UV-visible absorption spectra of product I and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 27] Figure 27 illustrates the UV-visible absorption spectra of product J and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 28] Figure 28 illustrates the UV-visible absorption spectra of product K and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Figure 29] Figure 29 illustrates the UV-visible absorption spectra of product L and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Diagram 30] Figure 30 illustrates the UV-visible absorption spectra of product M and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. [Diagram 31] Figure 31 illustrates the UV-visible absorption spectra of product N and two commercial references, namely TiO2 (MT-100TV from Tayca) and (BiO)2(CO3) from Alfa Aesar, obtained at a particle weight concentration of 0.01%. EXAMPLES
[0238] Example 1: Synthesis of bismuth oxycarbonate particles according to the present invention
[0239] Example 1.A: Solvothermal synthesis of crystallized particles A using (NH4)2CO3 and D-mannitol (0.25M) at 100°C
[0240] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M) and D-mannitol (0.25 M) is prepared in 50 ml of water and stirred until the reagents are completely dissolved.
[0241] Then, 10 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 100° C. for 12 hours.
[0242] Product A is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0243] Product A is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0244] Example 1.B: Solvothermal synthesis of crystallized particles B using urea and D-mannitol (0.25M) at 120°C
[0245] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M) and D-mannitol (0.25 M) is prepared in 50 ml of water and stirred until the reagents are completely dissolved.
[0246] Then, 10 ml of saturated urea solution (90 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 120° C. for 12 hours.
[0247] Product B is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0248] Product B is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0249] Example 1.C: Solvothermal synthesis of crystallized particles C using (NH4)2CO3 and D-mannitol (0.1M) at 150°C
[0250] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M) and D-mannitol (0.1 M) is prepared in 50 ml of water and stirred until the reagents are completely dissolved.
[0251] Then, 10 ml of supersaturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 150° C. for 12 hours.
[0252] Product C is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0253] Product C is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0254] Example 1.D: Reflux synthesis of crystallized particles D using (NH4)2CO3 and D-mannitol (0.1M) at 100°C.
[0255] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M) and D-mannitol (0.1M) is prepared in 50 ml of water and stirred until the reagents are completely dissolved. Subsequently, 10 ml of supersaturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100 °C for 8 h.
[0256] Product D is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0257] Product D is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0258] Example 1.E: Reflux synthesis of manganese-doped crystallized particles E using (NH4)2CO3 and D-mannitol (0.1M) at 100°C.
[0259] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M), manganese nitrate hydrate Mn(NO3)3·xH2O (0.004M) and D-mannitol (0.1M) is prepared in 50 ml of water and stirred until the reagents are completely dissolved.
[0260] Subsequently, 10 ml of supersaturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0261] Product E is isolated by centrifugation and washed alternately five times with water and ethanol, then dried in an oven at 60°C.
[0262] Product E is isolated in the form of a slightly pinkish white powder and is characterized by transmission electron microscopy and by UV / Vis spectrometry. Elemental analysis carried out on this product shows that the Bi / Mn molar ratio is 95:5.
[0263] Example 1.F: Reflux synthesis of a mixture of amorphous and crystallized particles F using urea and propylene glycol at 170°C.
[0264] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.015M) was prepared in 130 ml of propylene glycol until the reagent was completely dissolved.
[0265] Subsequently, 10 ml of a solution of urea (20 equivalents relative to bismuth) in propylene glycol is added and the mixture is heated at 180° C. for 1 hour.
[0266] Product F is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0267] Product F is isolated and characterized by transmission electron microscopy and by UV / Vis spectrometry.
[0268] Example 1.G: Synthesis of iron-doped crystallized particles G using (NH4)2CO3 and D-mannitol (0.1M) at 100°C
[0269] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M), ferric nitrate Fe(NO3)3·9H2O (0.002M) and D-mannitol (0.1M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0270] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A yellow solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0271] Product G is isolated by centrifugation and washed three times with alternating water and ethanol, then dried in an oven at 60°C.
[0272] Product G is isolated in the form of a pale yellow powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0273] Example 1. G': Synthesis of iron-doped crystallized particles G' using (NH4)2CO3 and D-mannitol (0.5M) at 100°C
[0274] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M), ferric nitrate Fe(NO3)3·9H2O (0.002M) and D-mannitol (0.5M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0275] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A yellow solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0276] Product G' is isolated by centrifugation and washed three times alternately with water and ethanol, then dried in an oven at 60°C.
[0277] Product G' is isolated in the form of a pale yellow powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0278] Example 1.H: Synthesis of chlorine-doped crystallized particles H using (NH4)2CO3 and D-mannitol (0.1M) at 100°C
[0279] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M), potassium chloride KCl (0.004 M) and D-mannitol (0.1 M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0280] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0281] Product H is isolated by centrifugation and washed three times alternately with water and ethanol, then dried in an oven at 60°C.
[0282] Product H is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0283] Example 1. H': Synthesis of chlorine-doped crystallized particles H' using (NH4)2CO3 and D-mannitol (0.5M) at 100°C
[0284] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M), potassium chloride KCl (0.004 M) and D-mannitol (0.5 M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0285] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0286] Product H' is isolated by centrifugation and washed three times alternately with water and ethanol, then dried in an oven at 60°C.
[0287] Product H' is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0288] Example 1.I: Synthesis of iodine-doped crystallized particles I using (NH4)2CO3 and D-mannitol (0.1M) at 100°C
[0289] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04 M), potassium iodide KI (0.004 M) and D-mannitol (0.1 M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0290] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0291] Product I is isolated by centrifugation and washed three times alternately with water and ethanol, then dried in an oven at 60°C.
[0292] Product I is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0293] Example 1. J: Synthesis of sulfate-doped crystallized particles J using (NH4)2CO3 and D-mannitol (0.1M) at 100°C
[0294] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M), ammonium sulfate (NH4)2SO4 (0.004M) and D-mannitol (0.1M) is prepared in 150 ml of water and stirred until the reagents are completely dissolved.
[0295] 30 ml of saturated ammonium carbonate solution (21 equivalents relative to bismuth) is added. A white solid precipitates. The mixture is then refluxed at 100° C. for 8 hours.
[0296] Product J is isolated by centrifugation and washed three times alternately with water and ethanol, then dried in an oven at 60°C.
[0297] Product J is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0298] Example 1. K: Solvothermal synthesis of crystallized particles K using Na2CO3 and D-mannitol (0.5M) at 150°C
[0299] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M) and D-mannitol (0.5M) is prepared in 25 ml of water and stirred until the reagents are completely dissolved. 5 ml of a saturated solution of sodium carbonate is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 150 °C for 12 hours.
[0300] Product K is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0301] Product K is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0302] Example 1. L: Solvothermal synthesis of crystallized particles L using Na2CO3 and glycerol / water mixture at 150 °C
[0303] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M) is prepared in 25 ml of a glycerol / water mixture (3:2 v / v) and stirred until the reagent is completely dissolved. 5 ml of a saturated solution of sodium carbonate is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 150 °C for 12 h.
[0304] Product L is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0305] Product L is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0306] Example 1. Solvothermal synthesis of crystallized particles M using M: Na2CO3 and ethylene glycol
[0307] A solution of bismuth nitrate pentahydrate Bi(NO3)3·5H2O (0.04M) is prepared in 25 ml of ethylene glycol and stirred until the reagent is completely dissolved. 5 ml of a saturated solution of sodium carbonate is added. A white solid precipitates. The mixture is then transferred to a Teflon autoclave reactor and heated at 150 °C for 12 hours.
[0308] Product M is isolated by centrifugation and washed five times alternately with water and ethanol, then dried in an oven at 60°C.
[0309] Product M is isolated in the form of a white powder and is characterized by transmission electron microscopy and by UV / Vis spectrophotometry.
[0310] Example 2: Morphology and size of bismuth oxycarbonate particles according to the present invention
[0311] The particle morphology for each product prepared according to Example 1 was determined by direct observation using a transmission electron microscope.
[0312] 1-5 milligrams of dried particles are dispersed in 10 ml of absolute ethanol and treated in an ultrasonic bath for 2 minutes.
[0313] 5 μl of the dispersion is then placed on a viewing grid (copper with a carbon surface layer) and allowed to dry in ambient air.
[0314] Observations are performed using a Hitachi HT 7700 transmission electron microscope at an accelerating voltage of 100 kV.
[0315] Images of Products A to M prepared in Example 1 are presented in Figures 1 to 15.
[0316] The average size is obtained by measuring the particle size by image analysis using the software ImageJ (C A Schneider, W S Rasband, K W E Liceiri, NIH Image to ImageJ: 25 years of image analysis, Nat. Methods. 9 (2012) 671-675).
[0317] The results are summarized in Table 1 below.
[0318] [Table 1]
[0319] The bismuth oxycarbonate particles synthesized according to the present invention are all in the form of tubes, plates, rods and / or combinations thereof, with the largest dimension of each particle being less than 400 nm.
[0320] Example 3: Preparation of a dispersion containing crystallized bismuth oxycarbonate particles A according to the present invention
[0321] A dispersion of crystallized bismuth oxycarbonate particles A according to Example 1.A was prepared in water / propylene glycol / Tween 登録商標 20 / xanthan gum mixture.
[0322] Water / Propylene Glycol / Tween 登録商標 The mixture of 20 / xanthan gum is added directly at ambient temperature to an accurately weighed mass of powder of Particle A. The suspension is then stirred magnetically for 10 minutes, exposed to ultrasound for 15 minutes, and then stirred again magnetically for 16 hours.
[0323] The weight percentages of the components based on the total weight of the composition are provided in Table 2 below.
[0324] [Table 2]
[0325] The resulting dispersion is fluid and white in color.
[0326] Example 3': Preparation of Dispersion N Comprising Crystallized Bismuth Oxycarbonate Particles A According to the Invention
[0327] A dispersion of crystallized bismuth oxycarbonate particles A according to Example 1.A and a dispersion of titanium dioxide MT-100-TV were prepared in a water / propylene glycol / Tween 1. 登録商標 It is prepared in a mixture of 20 / 51 of Basic Red.
[0328] Water / Propylene Glycol / Tween 登録商標 This mixture of 20 / 51% Basic Red is added directly to an accurately weighed mass of Particle A powder and titanium dioxide MT-100-TV at ambient temperature. The suspension is then stirred magnetically for 10 minutes, exposed to ultrasound for 15 minutes, and then stirred again magnetically for 16 hours.
[0329] The dispersion is then mixed with water / propylene glycol / Tween 登録商標 The resulting dispersion is diluted to 0.01% by weight (i.e. 0.005% by weight for particles A according to Example 1.A and 0.005% by weight for titanium oxide) with a medium of 0.20. The resulting dispersion is stirred for 20 minutes with magnetic stirring before carrying out the absorbance measurement.
[0330] The weight percentages of the components relative to the total weight of the composition are provided in Table 2A below.
[0331] [Table 2A]
[0332] The resulting dispersion is viscous and pale orange in color.
[0333] Example 4: Preparation of Dispersions Containing Bismuth Oxycarbonate or Titanium Dioxide Particles
[0334] Dispersions of bismuth oxycarbonate particles A to M according to Example 1, crystallized bismuth oxycarbonate particles not according to the invention, and titanium dioxide particles were prepared in a water / propylene glycol / Tween 100 ml dispersion. 登録商標 Prepared in a mixture of 20.
[0335] First, an accurately weighed amount of the powder is mixed with water / propylene glycol / Tween 登録商標 A 0.10 wt % dispersion is prepared by adding a mixture of 20.
[0336] The dispersion is subjected to ultrasound for 15 minutes and then stirred with a magnetic stirrer for 16 hours.
[0337] They were then diluted to 0.01 wt % (ie 0.005 wt % for particles G') and stirred again with magnetic stirring for 20 min, after which absorbance measurements were performed.
[0338] The weight percentages of the components relative to the total weight of the dispersion are provided in Table 3 below.
[0339] [Table 3]
[0340] The resulting dispersions are fluid and white, except for dispersions G and G', which are pale yellow.
[0341] Example 5: Absorbance spectra of bismuth oxycarbonate particles according to the invention and commercially available particles
[0342] The UV-visible absorbance spectrum of bismuth oxycarbonate particles according to the invention, prepared according to Example 1, was generated and compared with the absorbance spectra of two nanoscale references: (BiO)2CO3 (Alfa Aesar, plate-shaped, average dimensions: L, l≈500 nm and e=50 nm) and nanometric TiO2 treated with aluminum hydroxide and stearic acid (MT-100 TV from Tayca).
[0343] The absorbance spectrum for the dispersion prepared in Example 4 was obtained by a UV-Visible spectrophotometer.
[0344] The quartz cells used for absorbance measurements have sides of 1 cm. The spectrophotometer used is a Genesys 10S from Thermo Fischer Scientific.
[0345] Above a certain threshold UV absorbance measurement, filtering of UV radiation is considered effective, in particular particles having a UV absorbance threshold of greater than 0.5 in the dispersion medium in which they are contained are considered effective for filtering UV radiation.
[0346] The absorbance spectra are presented in Figures 16-30.
[0347] The results are summarized in Table 4 below.
[0348] [Table 4]
[0349] The absorbance spectrum of the bismuth oxycarbonate particles according to the invention is similar to that obtained for TiO2 particles over the entire UV range from 220 to 400 nm, especially in the UVB range.
[0350] The absorbance spectrum also shows that the bismuth oxycarbonate particles according to the present invention have high transparency in the visible region of 400 to 780 nm.
[0351] (BiO)2CO3 from Alfa Aesar has a constant absorbance value of 0.2, which is low, indicating that bismuth oxycarbonate particles with dimensions greater than 400 nm are unable to adequately filter the entire UV range.
[0352] In contrast, the use of bismuth oxycarbonate particles in accordance with the present invention improves the absorbance of UV radiation, thereby indicating effective filtering of UV.
[0353] Example 6: Absorbance spectra of bismuth oxycarbonate particles according to the invention and commercially available particles
[0354] The UV-visible absorbance spectrum of bismuth oxycarbonate particles according to the invention, prepared according to Example 1, was generated and compared with the absorbance spectra of two nanoscale references: (BiO)2CO3 (Alfa Aesar, plate-shaped, average dimensions: L, l≈500 nm and e=50 nm) and nanometric TiO2 treated with aluminum hydroxide and stearic acid (MT-100 TV from Tayca).
[0355] The absorbance spectrum for the dispersion prepared in Example 3' was obtained by a UV-Visible spectrophotometer.
[0356] The quartz cells used for absorbance measurements have sides of 1 cm. The spectrophotometer used is a Genesys 10S from Thermo Fischer Scientific.
[0357] Above a certain threshold UV absorbance measurement, filtering of UV radiation is considered effective, in particular particles having a UV absorbance threshold of greater than 0.5 in the dispersion medium in which they are contained are considered effective for filtering UV radiation.
[0358] The absorbance spectrum is presented in FIG.
[0359] The results are summarized in Table 5 below.
[0360] [Table 5]
[0361] The absorbance spectrum (FIG. 31) shows that the use of bismuth oxycarbonate particles in combination with a colorant in accordance with the present invention provides effective filtering of UV radiation.
Claims
1. For filtering ultraviolet radiation, the empirical formula is (BiO) 2-x (CO 3 ) where -0.4<x<0.6, wherein the maximum average dimension of the particles is less than 400 nm.
2. 2. Use according to claim 1 for filtering UVB radiation.
3. 3. The use according to claim 1 or 2, wherein the bismuth oxycarbonate particles are crystallized.
4. The bismuth oxycarbonate particles have the following formula (BiO): 2 (CO 3 The use according to any one of claims 1 to 3, wherein the
5. The use according to any one of claims 1 to 4, wherein the particles have a maximum average dimension of 300 nm or less.
6. The use according to any one of claims 1 to 5, wherein the particles are in the form of tubes, plates and / or rods.
7. 7. Use according to any one of claims 1 to 6, wherein the particles are predominantly or exclusively of platelet morphology and have an average length L in the range of 15 to 300 nm, in particular in the range of 30 to 250 nm; an average width l in the range of 10 to 250 nm, in particular in the range of 20 to 200 nm; and an average thickness e in the range of 2 to 120 nm, in particular in the range of 5 to 100 nm, with e<l<L.
8. 7. The use according to any one of claims 1 to 6, wherein the particles are predominantly or exclusively rod-like in morphology and have an average length L in the range of 30 to 300 nm, in particular in the range of 50 to 250 nm; a diameter d in the range of 15 to 150 nm, in particular in the range of 20 to 130 nm, and L>d.
9. 7. The use according to any one of claims 1 to 6, wherein the particles are predominantly or exclusively of tubular morphology and have an average length L in the range of 10 to 300 nm, in particular in the range of 20 to 250 nm; a diameter d in the range of 2 to 30 nm, in particular in the range of 3 to 20 nm, and L>d.
10. The particles are doped, in particular with cations derived from elements selected from titanium, vanadium, manganese, iron, copper, zinc, lanthanum and / or cerium, more preferably from elements selected from manganese, iron and / or cerium, even more preferably from elements selected from manganese or iron, and / or doped with S 2- , S.O. 3 2- , S.O. 4 2- , Cl - And / or I - an anion selected from, preferably SO 3 2- , S.O. 4 2- and / or Cl - anions selected from the group consisting of: - or SO 4 2- The use according to any one of claims 1 to 9, wherein the anion is doped with an anion selected from the group consisting of:
11. The use according to any one of claims 1 to 9, wherein the particles are undoped.
12. A composition, in particular a cosmetic composition, comprising: i) bismuth oxycarbonate particles according to any one of claims 1 to 11; ii) at least one aqueous phase and / or at least one fatty phase; and, iii) a) UV screening agents other than said bismuth oxycarbonate particles i); b) colorants; c) cosmetic active agents for caring for keratinous materials; d) surfactants; e) thickeners; and combinations thereof. The composition comprising at least
13. 13. Cosmetic composition according to claim 12, comprising from 0.5% to 40% by weight, preferably from 1% to 30% by weight, and even better still from 2% to 20% by weight of bismuth oxycarbonate particles relative to the total weight of the composition.
14. A non-therapeutic cosmetic method for filtering UV radiation, in particular UVB radiation, comprising the steps of: 2-x (CO 3 ) where -0.4<x<0.6, wherein the maximum average dimension of the particles is less than 400 nm.
Citation Information
Patent Citations
Whitening cream with self-protection function and preparation method thereof
CN113768810A
Aqueous composition for darkening keratin substance
JP1981154410A
Cosmetic compounded with bismuth compound
JP1994329524A
Cosmetic having ultraviolet light-shielding effect
JP1996259425A
Metal oxide particle and its use
JP2005263612A